The effects of firm age and firm size on the propensity of alliance formation. - Ong, Bee Chin. (2008)
This study examines factors influencing strategic alliance formation. Specifically, we explore the effects of firm age, firm size, and their interaction on firms’ propensity to form alliances. Event history analysis of (number) U.S firms listed on the New York Stock Exchange and NASDAQ that were on the market for strategic alliances from 1990 to 1996 reveals that firm age negatively affected a firm’s propensity to form alliances while firm size was positively related to a firm’s propensity to form alliances. For the interaction effect, we found that young and small firms and old and large firms have greater propensity to form strategic alliances than the rest. We explore the research implications of our results for future studies on strategic alliance formation, as well as managerial implications for firms looking to form alliances.